Metal–organic framework MIL-53(Fe): facile microwave-assisted synthesis and use as a highly active peroxidase mimetic for glucose biosensing1. Issue 23 (13th March 2015) - Dong, Wenfei; Liu, Xidong; Shi, Wenbing; Huang, Yuming
<x xml:space="preserve">Abstract</x> A microwave-based simple, fast and facile preparation of MIL-53(Fe) with an enhanced peroxidase-like activity for the highly sensitive and selective detection of glucose in real human serum samples was demonstrated.